Preparation and Characterization of Multifunctional Chitin/Lignin Materials. (30th September 2013) - Klapiszewski, Łukasz; Wysokowski, Marcin; Majchrzak, Izabela; Szatkowski, Tomasz; Nowacka, Magdalena; Siwińska-Stefańska, Katarzyna; Szwarc-Rzepka, Karolina; Bartczak, Przemysław; Ehrlich, Hermann; Jesionowski, Teofil
Abstract : Multifunctional chitin/lignin materials were synthesized. In order to combine mechanical milling of the biopolymers with simultaneous mixing, a centrifugal ball mill was utilized. The resulting materials, differing in terms of the proportions of precursors used, underwent detailed physicochemical and dispersive-morphological analysis. On the basis of FT-IR spectra and results of elemental analysis, the efficiency of the preparation of the materials was determined. The influence of the precursors on the thermal stability of the resulting systems was also evaluated. Zeta potential was determined as a function of pH to describe the electrokinetic stability of aqueous dispersions. This is important for evaluating the utility of the materials and indirectly confirms the effectiveness of the proposed method of synthesis of chitin/lignin products. Measurements were performed to determine basic colorimetric parameters, crucial in the production technology of multiple colored materials. It is expected that chitin/lignin materials will find a wide range of applications (biosorbents, polymer fillers, and electrochemical sensors), as they combine the unique properties of chitin with the specific structural features of lignin to provide a multifunctional material.